Detecting phenology change in the mayfly Ephemera danica: responses to spatial and temporal water temperature variations - Everall, Nicholas C.; Johnson, Matthew F.; Wilby, Robert L.; Bennett, Cyril J. (Wiley, 2015)
1. Rising water temperatures under climate change are expected to affect the phenology of aquatic insects, including the mayfly Ephemera danica Müller which is widespread throughout Europe.